Memory Training Anagram terhadap Peningkatan Fungsi Konitif Lansia - Herry Prasetyo; Petrus Nugroho D.S; Ulfah Agus Sukrillah (Jurnal Riset Kesehatan, 2015)
Research objective is to determine the effect of memory training: anagram toward the improvement of cognitive function in the elderly in nursing homes Catur Nugraha Kaliori, Banyumas. Sampling study conducted purposive sampling with the inclusion criteria including the age of 60-74 years, at least primary school education, and able to communicate well. The data collection was done before and after memory training: assessment anagram using the MMSE (Mini Mental State Examination). The data collection were analyzed by using Mc. Neemar Test and Chi Square Test. The results was based on Mc. Neemar Test, the intervention group has data ρ value = 0,001 (p less than 0,05) and the control group has ρ value = 0,031(p less than 0,05), therefore the score ρ value of the intervention group is more significant to increase the cognitif function of the elderly. Moreover, according to Chi Square test can be concluded that ρ value = 0,018 with (p less than 0,05), it means Ho was rejected and Ha was accepted, then, there is a difference value between the intervention group and the control group. Conclusion can be drawn that Memory Training: Anagram can improve cognitive function in the elderly more greater than Brain Gym.